2022
DOI: 10.3390/vaccines11010094
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Cultural Factors That Affect General Vaccination and COVID-19 Vaccination Attitudes

Abstract: The development of COVID-19 vaccines is a major scientific accomplishment that has armed communities worldwide with powerful epidemic control tools. Yet, COVID-19 vaccination efforts in the US have been marred by persistent vaccine hesitancy. We used survey methodology to explore the impact of different cognitive and cultural factors on the public’s general vaccination attitudes, attitudes towards COVID-19 vaccines, and COVID-19 vaccination status. The factors include information literacy, science literacy, at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…For example, media literacy is likely to have significant relevance during the COVID-19 pandemic given the abundance of online information about COVID-19 vaccines and treatments [ 60 ]. Finally, some have advocated for measures of vaccine confidence to assess health care trust at the system and provider levels [ 16 , 27 ]. The aVCI tool we used was brief, specific to COVID-19, and did not provide such an assessment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, media literacy is likely to have significant relevance during the COVID-19 pandemic given the abundance of online information about COVID-19 vaccines and treatments [ 60 ]. Finally, some have advocated for measures of vaccine confidence to assess health care trust at the system and provider levels [ 16 , 27 ]. The aVCI tool we used was brief, specific to COVID-19, and did not provide such an assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Many factors influence vaccination acceptance, including confidence in efficacy and safety, the perception of risks and benefits, and availability, as well as political, cultural, and religious factors [ 14 , 15 , 16 ]. Vaccine confidence is defined as the degree of trust individuals have in a specific vaccine and the health care system recommending vaccination [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, education levels have been shown to be a contributing factor, with those attaining higher levels of education showing a decrease in vaccine refusal or hesitancy ( 7 , 20 , 21 ). Keselman and colleagues ( 22 ) found that, “It is likely that information literacy and science literacy influenced public health trust and positive attitudes toward science, mediating their impact on positive attitude toward vaccination.” Separately, Biasio ( 23 ) suggested that, “Obstacles to vaccination might be overcome by improving health education, especially when targeted, not only at parents and adult populations but also at students, starting from primary and secondary schools, as recently suggested.” There are some studies that suggest the opposite trend. For example, a study from Thailand showed that increasing vaccine literacy among health care workers was not associated with vaccine acceptance ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a study by Liddon et al conducted on a sample of 1268 parents of children between the ages of 11 and 17 indicated that a high level of parental trust in the pediatrician has a powerful influence on the willingness to vaccinate a child against HPV [63]. At the same time, it is important to note that trust is a complex and multi-dimensional concept that various factors, such as communication style, cultural beliefs, and personal experiences, can influence [64][65][66]. Therefore, children's physicians must engage in active communication on cervical cancer risk and preventive measures with parents/caregivers.…”
Section: Discussionmentioning
confidence: 99%